(untitled) (Revista Apotheke, 2024)
This article presents an experience report based on performative pedagogy (Garoian, 1999) entitled: The teacher is present, with the aim of proposing a reperformance (Fornaciari, 2010) based on Marina Abramovic’s work entitled: The artist is present. The proposal is part of the attempts to develop a pedagogical plan that distances itself from the practices of docilization of bodies in the school environment, and is part of the trajectory of research into other ways of experiencing the body and the classroom as a place of creation. This section provides an overview of performative pedagogy and the studies of educator Rachel (2014) in the schools where she works in São Paulo. This is followed by an analysis of the experience, together with the students’ reports and the experience itself, dealing with performance theory as a place between art and school, student and teacher. Also, with the expectation of bringing these statutes and performance closer together, we opted for the concept of the threshold (Garoian, 1999), performance issues according to Schechner (2011) and aspects considered in the disturbational art approach (Danto, 2014). This report aims to problematize the school as a disciplinary place (Foucault, 1987) to contribute to a debate on arts teaching practices with a view to performative pedagogy.